Pemodelan Dinamika Kendaraan dengan Jaringan Syaraf Tiruan - Satrio Dewanto (Bina Nusantara University, 2014)
Creating autonomous vehicle that can drive without a driver is a dream of the researchers who see the application of such a system will be needed in the future. Realizing such a system requires a dynamic model of the vehicle. It may be obtained by analytical method using dynamic equations. However, this way is rather difficult to do, especially in modeling the non-linear factors caused by tires, suspension, road conditions, etc. This study, in order to avoid difficulties in the analytical method, used artificial neural networks to model the dynamic system of the autonomous vehicle. It utilized data input from the camera sensor and vehicle speed.